The evolution of Squalius alburnoides (Teleostei: cyprinidae) populations in the northern Iberian Peninsula : a molecular genetics and morphological approach into the past and present dynamics of an hybrid complex - Cunha, Carina João Alves da, 1975- (2010)
Tese de doutoramento em Biologia (Biologia Evolutiva), apresentada à Universidade de Lisboa através da Faculdade de Ciências, 2009